Contemporary Sub-Saharan Africa – Crisis of Post-colonial State and Famine (Czech Journal of International Relations, 1999)
Alex de Waal: Famine Crimes: Politics & the Disaster Relief Industry in Africa. James Currey, Oxford 1997,237 stran, ISBN 0-85255-810-4. Jean-Franois Bayart, Stephen Ellis & Béatrice Hibou: The Criminalization of the State in Africa. James Currey, Oxford 1999, 126 stran, ISBN 0-85255-812-0.